2021
DOI: 10.3390/ijms22041800
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Octapeptide Repeats on Prion Folding and Misfolding

Abstract: Misfolding of prion protein (PrP) into amyloid aggregates is the central feature of prion diseases. PrP has an amyloidogenic C-terminal domain with three α-helices and a flexible tail in the N-terminal domain in which multiple octapeptide repeats are present in most mammals. The role of the octapeptides in prion diseases has previously been underestimated because the octapeptides are not located in the amyloidogenic domain. Correlation between the number of octapeptide repeats and age of onset suggests the cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…32,33 Yu et al constructed mouse prion proteins without and with one or seven octapeptide repeats and found that deletion or insertion of the prion Nterminal octapeptide repeats increased the structural proportion of the C-terminal α helix, and prion protein containing 7 octapeptide repeat units converted significantly more protofibrils and provided partial protease resistance. 34 To verify whether HA5-68 binds to the octapeptide repeat region of PrP C , the whole octapeptide repeat region, peptide OR-41 (residues 51-91) was synthesized and used to compete with the binding between HA5-68 and PC-3 cells. As shown in Figure 3A, 2 μM peptide OR-41 greatly reduced the level of binding of 20 nM HA5-68 to PC-3 cells by approximately 97.96%, but the control peptide (Pep-Ctr) at the same concentration did not affect the binding of HA5-68 to PC-3 cells.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 Yu et al constructed mouse prion proteins without and with one or seven octapeptide repeats and found that deletion or insertion of the prion Nterminal octapeptide repeats increased the structural proportion of the C-terminal α helix, and prion protein containing 7 octapeptide repeat units converted significantly more protofibrils and provided partial protease resistance. 34 To verify whether HA5-68 binds to the octapeptide repeat region of PrP C , the whole octapeptide repeat region, peptide OR-41 (residues 51-91) was synthesized and used to compete with the binding between HA5-68 and PC-3 cells. As shown in Figure 3A, 2 μM peptide OR-41 greatly reduced the level of binding of 20 nM HA5-68 to PC-3 cells by approximately 97.96%, but the control peptide (Pep-Ctr) at the same concentration did not affect the binding of HA5-68 to PC-3 cells.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Creutzfeldt–Jakob disease (CJD) is the most common form of prion disease in humans. More and more literature studies have documented that 1 to 9 (except 3) additional repeats occur in the octapeptide repeat region, depending on the type of CJD. , Yu et al constructed mouse prion proteins without and with one or seven octapeptide repeats and found that deletion or insertion of the prion N-terminal octapeptide repeats increased the structural proportion of the C-terminal α helix, and prion protein containing 7 octapeptide repeat units converted significantly more protofibrils and provided partial protease resistance …”
Section: Resultsmentioning
confidence: 99%
“…Even in these cases, neuroimaging did not show typical features of CAA. To date, there is no clear evidence of association between a single OPRI and CAA, but a recent study showed that insertion of octapeptides, even if not located in the amyloidogenic domain, may weaken the α‐helical PrP structure, promoting the formation of prion amyloid fibrils [39].…”
Section: Discussionmentioning
confidence: 99%
“…PrP-C is a glycosyl phosphoinositol anchored membrane glycoprotein. Its N-terminal moiety presents a variable number of octapeptide repeats enriched in Glycine residues [104][105][106] forming the LCD of PrP. Traditionally, low complexity regions displaying infectivity have been often referred to as prion-like domains [1,2,5,6,8,9,73].…”
Section: Prp: the Protein That Started It Allmentioning
confidence: 99%
“…However, it required a longer incubation time and resulted in a lower PrP titer compared to the overexpression of the full-length version. Insertion of multiple octapeptide repeats increases the flexibility of the structure, weakening the α-helix in the C-terminal domain, thus promoting aggregation [105,109]. This evidence suggests that, whilst the N-terminal LCD of PrP-C is not essential for prion replication, it does have an effect on the rate of prion accumulation.…”
Section: Prp: the Protein That Started It Allmentioning
confidence: 99%